Case report of a family with hereditary inclusion body myopathy with VCP gene variant and literature review - Greta Asadauskaitė; Ramunė Vilimienė; Vytautas Augustinavičius; Birutė Burnytė (Frontiers in Neurology, 2023)
BackgroundMissense VCP gene variants lead to a disruption in protein homeostasis causing a spectrum of progressive degenerative diseases. Myopathy is the most frequent manifestation characterized by slowly progressing weakness of proximal and distal limb muscles. We present a family with myopathy due to c.277C > T variant in VCP gene.Case presentationThe patient‘s phenotype includes symmetrical muscle wasting and weakness in the proximal parts of the limbs and axial muscles, a wide based gait, lordotic posture, positive Gowers’ sign, mild calf enlargement, impaired mobility, elevated CK, and myopathy in proximal limb muscles. Whole body MRI revealed fatty replacement, predominantly affecting right vastus intermedius and medialis, gastrocnemius and soleus in calf, abdomen wall and lumbar muscles. Next-generation sequencing analysis revealed a pathogenic heterozygous variant c.277C > T (p.(Arg93Cys)) in exon 3 of the VCP gene. Segregation analysis showed that the detected variant is inherited from the affected father who developed symptoms at 60.ConclusionThe patients described experienced muscle wasting and weakness in the proximal and distal parts of the limbs which is a common finding in VCP related disease. Nevertheless, the patient has distinguishing features, such as high CK levels, early onset of the disease, and rapid mobility decline.